Analisis Jaringan Pipa Distribusi Air Baku WTP1 Waduk Gongseng Kabupaten Bojonegoro Provinsi Jawa Timur Menggunakan Qepanet - yulia indriani (Rekayasa Sipil, 2023)
The WTP 1 service area is planned to meet raw water needs in the Temayang and Sukosewu Districts with a raw water supply of 150 l/s. The research objective is to plan a pipeline network to help the people of Temayang and Sukosewu Districts meet their clean water needs. The pipeline network is planned using the QEpanet application to make it easier to describe the network and find out the elevation and length of the pipes. Hydraulic simulation using the Epanet application with the calculation of energy loss using the Hazen William method. The projected population is calculated using the arithmetic method. The pipeline network is planned to use pipes with a diameter of 76.2 – 406.4 mm. The pump is placed in WTP1 with a capacity of 150 l/s and a pump head of 130 m. From the results of the Epanet 2.2 hydraulic simulation on the Junc J22 branch, the pressure value is 1.19 m. so a pump is needed on the L22 pipe section.